Six Sigma: a goal‐theoretic perspective - Linderman, Kevin; Schroeder, Roger G.; Zaheer, Srilata; Choo, Adrian S. (Journal of Operations Management, 2003)
AbstractSix Sigma is a phenomenon that is gaining wide acceptance in industry, but lacks a theoretical underpinning and a basis for research other than “best practice” studies. Rigorous academic research of Six Sigma requires the formulation and identification of useful theories related to the phenomenon. Accordingly, this paper develops an understanding of the Six Sigma phenomena from a goal theoretic perspective. After reviewing the goal theory literature, these concepts, when applied to Six Sigma, suggest some propositions for future research. This paper can help serve as a foundation for developing scientific knowledge about Six Sigma.